2012
DOI: 10.1017/s1365100511000514
|View full text |Cite
|
Sign up to set email alerts
|

Does the Capital Intensity Matter? Evidence From the Postwar Japanese Economy and Other Oecd Countries

Abstract: The capital intensity takes an important role in two-sector and multisector growth models. Surprisingly very few empirical studies have been conducted so far except by Kuga (1967). This fact implies that few people have ever tried to perform any empirical research to study whether the two-sector and multisector optimal growth models could explain the economic development properly based on the empirical data. Although we witnessed fairly active theoretical research on two-sector and multisector growth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…As a result, when the investment sector becomes more intensive in physical capital relative to the consumption sector, the economic growth rate goes up. This is consistent with Takahashi et al (2012), who show that the investment good sector was capital intensive with respect to the consumption good sector (ε < 0) during the high speed growth period in Japan.…”
Section: Lemmasupporting
confidence: 91%
See 1 more Smart Citation
“…As a result, when the investment sector becomes more intensive in physical capital relative to the consumption sector, the economic growth rate goes up. This is consistent with Takahashi et al (2012), who show that the investment good sector was capital intensive with respect to the consumption good sector (ε < 0) during the high speed growth period in Japan.…”
Section: Lemmasupporting
confidence: 91%
“…This means that the apparent stability of the US global labor share hides contrasted evolutions of sectoral labor shares. More generally, Takahashi et al (2012) measure the capital intensity difference between consumption and investment good sectors in the main OECD countries. Focusing on the investment.…”
Section: Introductionmentioning
confidence: 99%
“…Using national accounting data on the most developed countries, Takahashi et al . () show that the aggregate consumption good sector is more capital intensive than the investment good sector.…”
Section: The Autarky Modelmentioning
confidence: 99%
“…Assumption 3 states that we consider dynamically efficient paths, that we restrain the share of capital in the economy s in order to get a positive value for α, and that we concentrate on a capital-intensive consumption good configuration. 7 Using national accounting data on the most developed countries, Takahashi et al (2012) show that the aggregate consumption good sector is more capital intensive than the investment good sector.…”
Section: Steady-state and Efficiency Propertiesmentioning
confidence: 99%
“…17 The restriction on the capital intensity difference across sectors is compatible with recent empirical evidence. Building on aggregate Input-Output tables, Takahashi et al [30] have shown that over the last 30 years the OECD countries have been characterized by a consumption good sector that is more capital-intensive than the investment good sector. See also Baxter [4] for similar results.…”
Section: Closed-economy Equilibriummentioning
confidence: 99%